Phenotypic and Molecular Biological Analysis of Polymycovirus AfuPmV-1M From Aspergillus fumigatus: Reduced Fungal Virulence in a Mouse Infection Model - Takahashi-Nakaguchi, Azusa; Shishido, Erika; Yahara, Misa; Urayama, Syun-ichi; Ninomiya, Akihiro; Chiba, Yuto; Sakai, Kanae; Hagiwara, Daisuke; Chibana, Hiroji; Moriyama, Hiromitsu; Gonoi, Tohru (Frontiers in Microbiology, 2020)
The filamentous fungal pathogen Aspergillus fumigatus is one of the most common causal agents of invasive fungal infection in humans; the infection is associated with an alarmingly high mortality rate. In this study, we investigated whether a mycovirus, named AfuPmV-1M, can reduce the virulence of A. fumigatus in a mouse infection model. AfuPmV-1M has high sequence similarity to AfuPmV-1, one of the polymycovirus that is a capsidless four-segment double-stranded RNA (dsRNA) virus, previously isolated from the genome reference strain of A. fumigatus, Af293. However, we found the isolate had an additional fifth dsRNA segment, referred to as open reading frame 5 (ORF5), which has not been reported in AfuPmV-1. We then established isogenic lines of virus-infected and virus-free A. fumigatus strains. Mycovirus infection had apparent influences on fungal phenotypes, with the virus-infected strain producing a reduced mycelial mass and reduced conidial number in comparison with these features of the virus-free strain. Also, resting conidia of the infected strain showed reduced adherence to pulmonary epithelial cells and reduced tolerance to macrophage phagocytosis. In an immunosuppressed mouse infection model, the virus-infected strain showed reduced mortality in comparison with mortality due to the virus-free strain. RNA sequencing and high-performance liquid chromatography (HPLC) analysis showed that the virus suppressed the expression of genes for gliotoxin synthesis and its production at the mycelial stage. Conversely, the virus enhanced gene expression and biosynthesis of fumagillin.　Viral RNA expression was enhanced during conidial maturation, conidial germination, and the mycelial stage. We presume that the RNA or translation products of the virus affected fungal phenotypes, including spore formation and toxin synthesis. To identify the mycovirus genes responsible for attenuation of fungal virulence, each viral ORF was ectopically expressed in the virus-free KU strain. We found that the expression of ORF2 and ORF5 reduced fungal virulence in the mouse model. In addition, ORF3 affected the stress tolerance of host A. fumigatus in culture. We hypothesize that the respective viral genes work cooperatively to suppress the pathogenicity of the fungal host.